Tinjauan Historis dan Perspektif Pengembangan Kelembagaan Irigasi di Era Otonomi Daerah - nFN Saptana; nFN Hendiarto; nFN Sunarsih; nFN Sumaryanto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2001)
EnglishThe primer mover of agriculture development consist of four factors, which are natural resources, human resource, technology, and institution. It is predicted that improvement of both food production and farm income will be driven by the following pressure factors: (1) The implication of globalization and liberalization, as well as international community coersion on environmental aspects; (2) The more limited of government expenditure, (3) The increase of natural resources scarcity and its degradtion, and (4) The launching of autonomy and its implication on decentralization of development. Historically, natural resources management has been managed partially through centralistic and top-down style. Deal with water resources management, the approach affected malfunction of local institution, the out comes was ineficient irrigation. Irrigation should be managed simultaneously both on supply and demand side. Refer to empirical studies it was convenient that enhancement of demand side management will increase food production and farm income significantly. It is useful to review irrigation performance, especially focused on institutional aspects. IndonesianAda empat faktor penggerak utama dalam pembangunan pertanian, yaitu sumberdaya alam, sumberdaya manusia, teknologi, dan kelembagaan. Upaya peningkatan produksi pangan dan pendapatan petani di hadapkan pada arus globalisasi ekonomi, pelestarian lingkungan, anggaran pembangunan yang terbatas, kelangkaan sumberdaya dan pelaksanaan otonomi daerah. Secara historis pengelolaan sumberdaya alam dengan pendekatan sentralistik (top down) telah berdampak pada memudarnya kelembagaan lokal dan inefisiensi pengelolaan sumberdaya alam dan air. Secara teoritis, pengelolaan air irigasi yang efisien membutuhkan pendekatan simultan yakni dari penyediaan air(supply management) dan dari sisi pemanfaatan (demand management). Secara empiris, pendekatan dari sisi pemanfaatan masih sangat membutuhkan perbaikan mempunyai peluang yang besar untuk dapat memberikan kontribusi yang nyata dalam peningkatan produksi pangan dan pendapatan petani. Tulisan ini bertujuan untuk melakukan tinjauan historis kelembagaan irigasi, mengidentifikasi faktor-faktor yang mempengaruhi kinerja kelembagaan irigasi, menarik benang merah yang merupakan simpul-simpul kritis dalam pengembangan kelembagaan irigasi, dan merumuskan pengembangan kelembagaan irigasi di era otonomi daerah.